A survey of the effects of aging on biometric identity verification - Lanitis, Andreas (My University, 2010)
The performance of biometric authentication systems is affected by discrepancies between data stored in biometric templates and corresponding data derived from the actual owners of biometric templates. Such discrepancies are mainly attributed to within-person variations of biometric features. Among all types of within-person variations, aging-related variation displays unique characteristics that make the process of dealing with aging a challenging task. In this paper we discuss how aging affects different types of biometric features and discuss possible approaches that aim to eliminate the effects of aging so that deterioration in the long-term performance of biometric authentication systems is minimised. © 2010 Inderscience Enterprises Ltd.
Keywords: aging effects; biometric templates; template update; multi-modal biometrics; person identification; biometric authentication; identity verification